MEASURING THE WORK INTEREST OF VOCATIONAL WORKERS IN ISLAMIC BANKS: WORK READINESS AS AN INTERVENING FACTOR OF WORK COMPETENCE AND MOTIVATION - Irsyadi, Muhammad Tegar (NISBAH: Jurnal Perbankan Syariah, 2025)
The Islamic banking industry in Indonesia has expanded markedly amid globalization and digitalization, with assets reaching IDR 801.3 trillion in 2023 a 13.34 percent year on year increase. Despite this growth, only 40 percent of vocational workers in Islamic banking satisfy industry competency standards, and 47.8 percent experience field job mismatch. At the workforce level, 90 percent hold non Islamic banking backgrounds, highlighting a misalignment between vocational workers and sector requirements. This study examines the effects of work competence, work motivation, and work readiness on the intent to pursue careers in Islamic banking among 125 vocational workers in Depok City. Employing a quantitative survey and partial least squares structural equation modeling a method suited to small samples and non-normally distributed data results reveal that work competence and readiness exert significant positive influences on career intent, whereas motivation significantly affects only readiness and not intent directly. Moreover, work readiness mediates the relationships between both competence and motivation and career intent. These findings inform strategic enhancements in vocational workers of Islamic Banking, targeted training, and recruitment policies to strengthen link and match outcomes for the Islamic banking workforce.